2018
DOI: 10.1145/3287049
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Needs in IoT Control and Accountability

Abstract: A key issue for smart home systems is supporting non-expert users in their management. Whereas feedback design on use cases (such as energy feedback) have gained attention, current approaches to providing awareness on the system state typically provide a rather technical view. Long-term investigations of the practices and resources needed for maintaining Do-It-Yourself smart home systems, are particularly scarce. We report on a design case study in which we equipped 12 households with DIY smart home systems fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 70 publications
0
14
0
2
Order By: Relevance
“…e new generation of learners is shifting from passive learning to active discovery and inquiry, from large-class teaching to personalized teaching, and from consumers of knowledge to creators of knowledge and has an increasing demand for the intelligent learning environment, ubiquitous learning resources, and personalized teaching. e key to contemporary teaching change is to meet the new needs of learners for teaching and learning styles, explore the possible utility of artificial intelligence technology in boosting education and teaching innovation, and crack the current problems in education development [5]. Our existing education is education extended from the industrial era and education aimed at cultivating knowledgeable and skilled people [6].…”
Section: Introductionmentioning
confidence: 99%
“…e new generation of learners is shifting from passive learning to active discovery and inquiry, from large-class teaching to personalized teaching, and from consumers of knowledge to creators of knowledge and has an increasing demand for the intelligent learning environment, ubiquitous learning resources, and personalized teaching. e key to contemporary teaching change is to meet the new needs of learners for teaching and learning styles, explore the possible utility of artificial intelligence technology in boosting education and teaching innovation, and crack the current problems in education development [5]. Our existing education is education extended from the industrial era and education aimed at cultivating knowledgeable and skilled people [6].…”
Section: Introductionmentioning
confidence: 99%
“…Jakobi et al [47] studied the issues faced by users adopting smart homes in a living lab. Jakobi et al [48] also reported a design case study with 12 households and found that users' accountability needs changed over time. Brush et al [11] found that manageability and unreliable behavior were major concerns for smart home users.…”
Section: User Experience In Smart Homesmentioning
confidence: 99%
“…Seven reported having an undergraduate degree, and five a graduate degree. Twelve participants were working age adults (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) and eight participants were schoolage children and young adolescents (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Two members were too young to participate (1-3).…”
Section: Participant Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…multiple accounts) to counter such imbalances. However, how these can be put into practice for the benefit of the whole household remains a question of ongoing research [3,2,4,1,8].…”
Section: Introductionmentioning
confidence: 99%